Concepções de boa postura dos participantes da Escola Postural da ESEF/UFRGS - Adriane Vieira; Jorge Luiz de Souza (Universidade Federal do Rio Grande do Sul, 2002)
In thisarticle, we present and discuss conceptions of good posture engendered in the master thesis titled "Corpority in Back School". The reflections are done based on a semistructured interview applied to ten participants inscribed in theextensionprogram Back School offered to the general community at ESEF/ UFRGS, in 1997. The analysis of the interviews allowed us to comprehend that the participants' conception of good posture is very similar to that disseminated in literature from XIX century on, which gives priority to the alignment and position of body segments, to muscular strength and strain, and to body control and discipline. More recent conceptions related to body perception are littlemen tioned by the subjects in terviewed.